Structural of Pedicle Screw on Biomechanical Characteristics of Spinal Scoliosis Correction Deformation - Weriono, Weriono; Rusli, Meifal; Dahlan, Hendery; Sahputra, Roni Eka (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2025)
Scoliosis correction methods often involve orthopedic procedures such as implant placement to stabilize movement and correct spinal deformity. The choice of surgical method is highly dependent on the location and nature of the fracture. Fractures with significant damage require a different approach compared to cases of minor injuries. Three dimensional finite element model of C1–L6 spine was used to simulate conditions with single cylindrical implant fixation under a vertical downward loading force 50 N and cylindrical screw types made of titanium alloy. The human spine, encompassing the cervical, thoracic, and lumbar regions, exhibits a complex biomechanical response when subjected to physiological loads. Displacement that occurs due to axial force can be the result of pedicle screw movement with vertebrae of the spine. Installation of 4 (four) rows of pedicle screws reduces the release of pedicle screws from the spine. The use of more fixation can reduce the stress distribution on the vertebrae of the spine.